Effect of Dietary Vegetable Sources Rich in Unsaturated Fatty Acids on Milk Production, Composition, and Cheese Fatty Acid Profile in Sheep: A Meta-Analysis - Vargas-Bello-Pérez, Einar; Darabighane, Babak; Miccoli, Florencia E.; Gómez-Cortés, Pilar; Gonzalez-Ronquillo, Manuel; Mele, Marcello (Frontiers in Veterinary Science, 2021)
A meta-analysis was conducted to analyze the effects of different dietary vegetable sources rich in unsaturated FA (UFA) on sheep cheese FA profile. This study also quantified the overall effect of feeding sheep with vegetable sources rich in UFA on milk yield (MY) and milk composition. A literature search was conducted to identify papers published from 2000 to 2019. Effect size for all parameters was calculated as standardized mean difference. Heterogeneity was determined using I2 statistic, while meta-regression was used to examine factors influencing heterogeneity. Effect size was not significant for MY, milk fat percentage (MFP) and milk protein percentage (MPP). Dietary inclusion of vegetable sources rich in UFA decreased effect size for C12:0, C14:0, and C16:0 and increased effect size for C18:0, C18:1 t-11, C18:1 c-9, C18:2 c-9, t-11, C18:2 n-6, and C18:3 n-3. Heterogeneity was significant for MY, MFP, MPP, and overall cheese FA profile. Meta-regression revealed days in milk as a contributing factor to the heterogeneity observed in MFP and MPP. Meta-regression showed that ripening time is one of the factors affecting cheese FA profile heterogeneity while the type of feeding system (preserved roughages vs. pasture) had no effect on heterogeneity. Overall, inclusion of dietary vegetable sources rich in UFA in sheep diets would be an effective nutritional strategy to decrease saturated FA and increase polyunsaturated FA contents in cheeses without detrimental effects on MY, MFF and MPP.